Morphology of seeds of some species of rare and endemic plants of Kazakhstan - Kubentayev, S.A.; Khasenova А.Е.; Imanbayeva А.А.; Alibekov, D.T. (Fundamental and Experimental Biology, 2022)
The article presents the results of the study of morphometric parameters and weight indicators of seeds of 18 species of rare and endemic plants listed in the Red Book of Kazakhstan: Adonis vernalis, A. volgensis, Astragalus glycyphyllos, Crataegus ambigua, Drosera rotundifolia, Fraxinus sogdiana, Lilium martagon, Malacocarpus crithmifolius, Incarvillea semiretschenskia, Paeonia anomala, P. intermedia, Rhodiola rosea, Leuzea carthamoides, Tulipa kolpakowskiana, T. patens, T. suaveolens, T. urumiensis, including 6 sub-endemic species (Crataegus ambigua, Fraxinus sogdiana, Malacocarpus crithmifolius, Tulipa kolpakowskiana, T. suaveolens, T. urumiensis) and one narrow-localised endemic (Incarvillea semiretschenskia). The characteristics of the shape, texture of the seed peel and the color of the seeds of the studied samples are similar to those studied earlier. Significant differences were found in the size and weight of 1000 seeds from previously published data, which, in our opinion, reflect the variability of traits that should be considered when identifying species.